More Than "A Room of Antiquities" at the Global Museum: Constructing New Meanings Through the Provenance Research of an Ancient Egyptian Legacy Collection. Issue 2 (June 2022) - Jiménez, Lissette M.; Fogarty, Christine A.; Luby, Edward M.
Non-systematically excavated archaeological legacy collections of antiquities are often undervalued or overlooked by museums because of their unknown provenience and questionable or problematic provenance. This article describes how extensive research into the provenance of an ancient Egyptian legacy collection purchased in Egypt in 1884 by Adolph Sutro that is now stewarded by the Global Museum at San Francisco State University exposes a new expansive research potential for the collection, enabling Museum Studies students and faculty and museum staff to construct innovative interpretive frameworks through integrated Museum Studies curriculum, educational public programming, and exhibitions of the collection in the museum. This case study underscores the importance of provenance research for contextualizing legacy collections and illustrates how this research can be a catalyst for important discussions of the antiquities trade, colonial collecting practices, public educational significance, and ethical collection stewardship, curation, and display.